Warriors. Tigerstar & Sasha. 2, Escape from the forest - Hunter, Erin (Warriors : Tigerstar & Sasha (Graphic novel), 2009)
Sasha has decided to forge a life outside of the Clans and away from Tigerstar's evil plots and plans. But life as a rogue is much harder than she expects, and Sasha soon starts to lose hope. Will she be forced to wander alone forever, scrapping for every meal and fighting with the cruel, territorial cats who dwell in the alleys of Twolegplace?